Pivotal Role of TGF-β/Smad Signaling in Cardiac Fibrosis: Non-coding RNAs as Effectual Players - Saadat, Somayeh; Noureddini, Mahdi; Mahjoubin-Tehran, Maryam; Nazemi, Sina; Shojaie, Layla; Aschner, Michael; Maleki, Behnaz; Abbasi-kolli, Mohammad; Rajabi Moghadam, Hasan; Alani, Behrang; Mirzaei, Hamed (Frontiers in Cardiovascular Medicine, 2021)
Unintended cardiac fibroblasts (CFs) proliferation in many pathophysiological heart conditions, known as cardiac fibrosis, results in pooling of extracellular matrix (ECM) proteins in the heart muscle. Transforming growth factor β (TGF-β) as a pivotal cytokine/growth factor stimulates fibroblasts and hastens ECM production in injured tissues. The TGF-β receptor is a heterodimeric receptor complex on the plasma membrane, made up from TGF-β type I as well as type II receptors, giving rise to Smad2 and Smad3 transcription factors phosphorylation upon canonical signaling. Phosphorylated Smad2, Smad3 and cytoplasmic Smad4 intercommunicate to transfer the signal to the nucleus, culminating in provoked gene transcription. Additionally, TGF-β receptor complex activation starts up noncanonical signaling that lead to the MAPK cascade activation, inducing p38, JNK1/2, and ERK1/2 signaling. TGF-β not only activates fibroblasts and stimulates them to differentiate into myofibroblasts, which produce extracellular matrix proteins, but also promotes fibroblast proliferation. Non-coding RNAs (ncRNAs) are important regulators of numerous pathways along with cellular procedures. MicroRNAs, circular long non-coding RNAs, combined with long non-coding RNAs are capable of affecting TGF-β/Smad signaling, leading to cardiac fibrosis. More comprehensive knowledge based on these processes may bring about new diagnostic and therapeutic approaches for different cardiac disorders.